Technology enhancements for spectacular elements in Mak Yong productions at Istana Budaya - Norzizi Zulkafli (Tanjong Malim, 2023)
Technology enhancements for spectacular elements in Mak Yong productions at Istana Budaya by Norzizi Zulkafli